Kinematics and movement variability related to service performance in young tennis players - Urbán, T.; Hernández-Davó, H.; Moreno, F. J. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Recent studies have focused on analyzing kinematics related to performance in precision skills and in tennis service in particular (Reid, Whiteside & Elliott, 2011). Regarding kinematics variability, some studies have analyzed this topic in sport skills (Wagner, et al. 2011). Nevertheless, few researches have addressed this problem in tennis shots. The aim of this study is to analyze the relationship between kinematic variables, movement variability and performance of the tennis service in young players. Methods: Twenty-nine young intermediate level tennis players (20 male, 9 female) (age 12.9 ± 1.64) took part in the study. All participants carried out twenty services towards a target located on the service box. Kinematic variables from the dominant hand, arm, hip and the non-dominant hand were collected (Polhemus Liberty 240Hz update rate). Ball speed (RS3600 radar) and radial error of ball bounces (video digitized) were recorded to assess service performance. Correlation analysis was carried out to analyze the relationship between kinematics, variability and performance. Results: Range of motion in the three axis correlated with higher velocity of the ball (r = .491; p=0.007; X axis), (r =.484; p=0.008; Y axis), (r = .608; p<0.001; Z axis). Right arm, hip and left hand position in Y axis also correlated with higher velocity values (r = .635; p<0.001; r = .517; p=0.004; r = .420; p=0.023, respectively). Ball velocity correlated negatively with variability of the hand in the X and Z axis at the beginning of the movement (r = -.417; p=0.024; r = -.529; p=0.003 respectively). Radial error correlated with standard deviation of movement velocity of the hand during middle of the movement in the Y axis (r =.432; p=0.019) and the Z axis (r =.466; p=0.011). Discussion: Higher range of motion and forward displacement of the dominant arm, hip and non-dominant hand has proved effective to increase the velocity of services. The variability of the movement affects the velocity of services only when this variability is observed at the beginning of the movement. Regarding service accuracy, the variability of the movement in the Y and Z axis reduces performance only if this variability is showed at the beginning or in the middle of the service movement.